Evaluation of the pilot phase of a Student Support Strategy to improve retention and completion rates of Aboriginal and Torres Strait Islander students. Issue 2 (5th December 2021) - Hearn, Shane; Funnell, Sarah
Abstract: Increasing Aboriginal and Torres Strait Islander participation in higher education can play a critical role in transforming lives and is the trajectory to closing the gap and reducing disadvantage. Despite recent progress, Aboriginal and Torres Strait Islander peoples remain significantly under-represented in higher education. Poor retention and high attrition rates of these students come at significant financial cost for the individual, community, university and government. Wirltu Yarlu, the Indigenous Education Unit at the University of Adelaide has reviewed the role student support services play in improving retention and completion rates, with an aim to improve Aboriginal and Torres Strait Islander student retention and completion. The newly developed Student Success Strategy is an innovative approach to student support that aims to identify and respond to individual student needs in a more effective and efficient manner. The model encompasses a self-assessment tool designed to measure progress across several domains. Self-assessments are used to inform student specific support needs which in turn enable support staff to personalise future interventions for each student and respond accordingly in an attempt to reduce and prevent student attrition.